2001
DOI: 10.1002/ar.1088
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between postsynaptic NK1 receptor distribution and nerve terminals innervating myenteric neurons in the guinea‐pig ileum

Abstract: The amounts of neurokinin 1 (NK 1 ) receptor immunolabelling on the membranes of myenteric cell bodies at appositions with tachykinin-immunoreactive nerve terminals, other nerve terminals, and glial cells were compared at the ultrastructural level using pre-embedding, double-label immunocytochemistry. NK 1 receptor immunoreactivity was revealed using silver-intensified, 1 nm gold, and tachykinin-immunoreactive nerve terminals were revealed using diaminobenzidine. The density of NK 1 receptor immunolabelling (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…We interpret the staining to be at the surface membranes of the neurons, although this localization can only be established by electron-microscopic analysis. In a previous study involving the electron-microscopic examination of NK1 receptor localization, the receptor was almost continuously present along the surface membrane, whereas presynaptic terminals were irregularly located around the neurons (Portbury et al 2001). Earlier electron-microscopic studies have also reported that only parts of the surfaces of enteric neurons are contacted by presynaptic terminals (Gabella 1972;Komuro et al 1982).…”
Section: Discussionmentioning
confidence: 94%
“…We interpret the staining to be at the surface membranes of the neurons, although this localization can only be established by electron-microscopic analysis. In a previous study involving the electron-microscopic examination of NK1 receptor localization, the receptor was almost continuously present along the surface membrane, whereas presynaptic terminals were irregularly located around the neurons (Portbury et al 2001). Earlier electron-microscopic studies have also reported that only parts of the surfaces of enteric neurons are contacted by presynaptic terminals (Gabella 1972;Komuro et al 1982).…”
Section: Discussionmentioning
confidence: 94%